The impact of dividend policy and climate change on share price volatility : a study on the plantation sector of Malaysia - Nirmal Kumaar, Mahindran (2018)
The objective of this research is to determine the impact of dividend policy and climate change on share price volatility on Malaysian Plantation sector companies listed on the Bursa Malaysia Main Board. The sample of this study consists of 33 Malaysian public listed plantation companies with 462 observations from the period of 2003 to 2016. To achieve the objective of this study, a panel data regression which is Fixed Effect model was used to analyse the dataset. Based on the regression results, it was found that dividend payout ratio (PAYOUT), dividend yield (DYIELD), market value (SIZE) and long-term debt (DEBT) negatively and significantly impacts share price volatility (PVOL). On the other hand, earnings volatility (EVOL) positively and significantly impacts share price volatility. Overall, all variables are significant to share price volatility except growth in assets (GROWTH) which is found to be negatively insignificant to share price volatility. Moreover, El Nino (ELN) and flood (FLD) which are found to be positively insignificant to share price volatility of Malaysian Plantations companies. Current results can be incorporated to the unoccupied literature field and can help as a foundational tip to the studies which will be carried out in the future.